Risk exposure to SARS-CoV-2 and workers’ risk perception in non-healthcare setting in Hong Kong, Nanjing and Wuhan: A qualitative multi-site study - Chui Lau, Janice Ying; Wang , Dongming; Tang , Jingyi; Wang , Shoulin; Yi Lee, Priscilla Ming; Yu Tang, Natalie Hiu; Wu , Tangchun; Shen , Hongbing; Ji, Xiaoming; Chen , Weihong; Ah Tse, Lap (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Introducción: Understanding risk perception that hinges on health-protective behaviors is central to strategies for prevention. Aim: To classify the pattern of potential risk of worker exposure to SARS-CoV-2, and to assess association with risk perception among non-healthcare workers Methods: In a multi-site, qualitative study, we conducted individual in-depth interviews and mini focus group discussions with employees, managerial staff and self-employees from Hong Kong (n=87), Nanjing (n=60), and Wuhan (n=60) between June 2020 and March 2021. Audios were transcribed and categorized by themes following Grounded Theory approach. Results: We identified seven major types of potential risk exposure pattern by category of parameters. The risk perceptions decreased among Type A workers, working at fixed location in office, and no/little contacts with clients/customers, and increased among workers having the concern of asymptomatic characteristics of SAR-CoV-2, daily contact with large size of the unfamiliar crowds, unhygienic behaviors of clients/customers, and use of public transportation to commute to work. The notion that the sense of safety deriving from the implementation and adherence with safety measures despite stringency, and trust with the government was most frequently reported in Nanjing and Wuhan. Conclusion: Study examines COVID-19 risks and risk perceptions among non-healthcare workers in three cities. Variations in risk perceptions were found, influenced by factors such as work patterns and safety measures. Trust in government and concerns about international contacts were common themes. The findings emphasize the need for targeted interventions, mental health support, and inclusive policies to address occupational health disparities and promote workplace safety.